Assessment of scoured bridges subjected to ship impact. (February 2022) - Irhayyim, Amir; Gunaratne, Manjriker; Fioklou, Ameh
Abstract: Two most common causes of bridge failure are hydraulic failure due to scour of the bridge foundation and collision of vessels. Scour has been the predominant cause of bridge failures in the US, accounting for 60% of them, and it is the loss of soil caused by high-velocity flowing water, adversely affecting the stiffness of bridges. It may also result in excessive rotation of the column and displacement of the deck. The second most common cause of bridge failure in the US is vessel collision, responsible for 12% of them. The above hazards are typically treated independently as single extreme events according to the American Association of State Highway and Transportation Officials (AASHTO) design guidelines. However, vessel collision with scoured bridge piers and piles can co-occur, and there is a lack of assessment methodologies to address this synchronous dual-hazard scenario. Based on past statistics, narrow and congested waterways are more prone to collisions between ships and bridges. The U.S. and the world are projected to experience an increase in ship sizes and higher frequencies of large vessel navigation in waterways due to global economic growth. Therefore, ship impact scenarios need closer scrutiny in the future. The aim of this research is to highlight and investigate potential bridge failures during the co-occurrence of scour and ship impact. The results of this research will help bridge engineers to address such risks. The results illustrate that depending on the surrounding soil properties, ship impact locations, nonlinear dynamic load time history, and scour depth conditions, shear demand of the column base decreases due to increased scour at lower impact locations with clay soil configuration. In addition, the moment demand on the bridge column increases with the scour depth. The results of the parametric studies show larger displacement in piles under increased scour and ship impact locations close to pile cap, especially for clayey soil foundations.